2020
DOI: 10.1186/s13045-020-00913-2
|View full text |Cite
|
Sign up to set email alerts
|

CD155 immunoregulation as a target for natural killer cell immunotherapy in glioblastoma

Abstract: Natural killer (NK) cells are powerful immune effectors, modulating their anti-tumor function through a balance activating and inhibitor ligands on their cell surface. Though still emerging, cancer immunotherapies utilizing NK cells are proving promising as a modality for the treatment of a number of solid tumors, including glioblastoma (GBM) and other gliomas, but are often limited due to complex immunosuppression associated with the GBM tumor microenvironment which includes overexpression of inhibitory recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 99 publications
0
51
0
Order By: Relevance
“…TIGIT is an inhibitory checkpoint receptor that has become the focus of much research due to its role in T cell and NK cell exhaustion when bound to CD155 (Dougall et al, 2017 ; O'Donnell et al, 2019 ). Notably, TIGIT is highly expressed in CD8+T cells, CD4+T cells, and NK cells during tumor infiltration (Song et al, 2018 ; Josefsson et al, 2019 ; Lupo and Matosevic, 2020 ). In this study, we found that TIGIT was highly expressed in tumor tissues and that high TIGIT expression predicted a more advanced disease stage and worse prognosis in PSCCE.…”
Section: Discussionmentioning
confidence: 99%
“…TIGIT is an inhibitory checkpoint receptor that has become the focus of much research due to its role in T cell and NK cell exhaustion when bound to CD155 (Dougall et al, 2017 ; O'Donnell et al, 2019 ). Notably, TIGIT is highly expressed in CD8+T cells, CD4+T cells, and NK cells during tumor infiltration (Song et al, 2018 ; Josefsson et al, 2019 ; Lupo and Matosevic, 2020 ). In this study, we found that TIGIT was highly expressed in tumor tissues and that high TIGIT expression predicted a more advanced disease stage and worse prognosis in PSCCE.…”
Section: Discussionmentioning
confidence: 99%
“…This combination addresses several aspects of tumor immune evasion outcomes, namely tumor antigen heterogeneity, the immunosuppressive environment, and insufficient intratumoral NK cell presence ( , accessed on 1 March 2021). This procedure is applicable to other markers that are pro-tumorigenic, such as CD155 [ 94 ], and might offer possible treatment strategies for further investigations.…”
Section: Nk Cells As a Possible Immunotherapy Approach To Treat Glmentioning
confidence: 99%
“…Although, the mechanism by which the CD226 receptors exert control over the function of NK cell is a challenge, the engagement of the receptor with CD155 in the transcription factor FOXO1 phosphorylation, which results in the inactivation of the receptor’s negative regulatory control over the effector function of NK cell. 226 , 240 …”
Section: Nk Cell As a Promising Therapeutic Target For Cancermentioning
confidence: 99%